Strengthening Digital Morals and Ethics among High School Students through the Civilized School Program: A Community Engagement Initiative at SMA Negeri 2 Plus Panyabungan - Jureid Jureid; Mufti Fahrizal Harahap; Azizatur Rahmah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
The increasing use of social media among adolescents presents challenges for character development in schools, particularly in digital communication ethics, responsible information sharing, cyberbullying, and self-regulation. This highlights the need to integrate digital literacy with character education to promote responsible online behavior. This community engagement program aimed to strengthen students’ digital morals and ethics through the Civilized School Program at SMA Negeri 2 Plus Panyabungan, Indonesia. The program involved 30 students from grades X–XII and used an educational-participatory approach supported by teachers and school staff. Activities included digital ethics counseling, training on healthy digital communication, cyberbullying case simulations, reflective discussions, student-led digital campaigns, and the formation of student character ambassadors. Program evaluation used a mixed-method design involving pretest-posttest questionnaires, observations, reflections, and teacher interviews. Quantitative results showed an increase in average scores from 60.1% to 87.1%, representing a 27.0 percentage-point improvement across five indicators: digital communication ethics, awareness of cyberbullying, social empathy, responsible social media use, and self-regulation. Qualitative findings indicated improved student behavior, including more cautious online communication, more selective information sharing, and greater respect for others’ opinions. Overall, the program contributed to fostering a more ethical and responsible digital culture within the school. The Civilized School Program demonstrates potential as a participatory school-based model for integrating digital literacy and character education among adolescents.